Desarrollo de un tensioactivo catiónico para fibras acrílicas mediante el proceso de sol-gel a nivel de laboratorio (2017)
The research of this project focused on finding the formulation of a cationic surfactant that can give acrylic fiber different properties such as hydrophilicity, smoothness, smoothness, volume and others. The aim is to replace the product, which today the consumer companies are forced to import generating an increase in the costs and production times of the acrylic fibers because in needing a softener they must make minimum orders of a container brought directly from Europe, Which generates high investments in the logistics chain, waiting times, man hours for logistics, inventory spaces in warehouses, control of batch expiration, costs in maritime and local transport, taxes and levies.